Victim-offender race and support for capital punishment: A factorial design approach - Applegate, Brandon K. (American journal of criminal justice, 1994)
Existing research suggests that juries are more likely to condemn murderers to death when offenders are black victims are white. It remains to be seen, however, whether these decisions reflect broader racial prejudices in society that are imported into the jury room. If they do, then insuring equity in capital sentencing may be beyond reach. Accordingly, this study uses factorial design methodology to examine whether members of the general public are more supportive of capital punishment when asked to rate a vignette describing a murder involving a white victim and black offender as opposed to other victim-offender racial combinations. Our analyses suggest that the race of the offender, but not the victim, has a significant influence on support for capital punishment. Thus, procedural safeguards alone may be unable to eliminate racial bias in capital sentencing.